Individual Differences in Sequence Learning Ability and Second Language Acquisition in Early Childhood and Adulthood. Issue 4 (16th August 2013) - Granena, Gisela
Abstract : Language aptitude has been hypothesized as a factor that can compensate for postcritical period effects in language learning capacity. However, previous research has primarily focused on instructed contexts and rarely on acquisition‐rich learning environments where there is a potential for massive amounts of input. In addition, the studies conducted to date have investigated cognitive aptitudes weighted heavily in favor of explicit processes (e.g., language analysis) and have overlooked potential individual differences in implicit cognitive processes. This study examines whether sequence learning ability (one aspect of a cognitive aptitude hypothesized to be relevant for implicit language learning and processing) is involved in early and late second language learners' morphosyntactic attainment, as measured by two types of structures and tasks. Results revealed that sequence learning ability moderated scores on structures involving grammatical agreement relations in both early and late second language learners.